2009
DOI: 10.1111/j.1365-2745.2009.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary ecology of vegetative dormancy in mature herbaceous perennial plants

Abstract: Summary1. I present an evolutionary ecology interpretation of vegetative dormancy in mature herbaceous perennials. This kind of vegetative dormancy has been noted for at least 40 years, but has only recently become a topic of study. 2. Vegetative dormancy may be considered in a life-history context. Both vegetative dormancy and mortality typically decrease with increasing size. Vegetative dormancy's relationship to reproduction is more complex, because some species increase flowering and fruiting after dormanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(130 citation statements)
references
References 93 publications
0
125
0
5
Order By: Relevance
“…However, the plant kingdom encompasses a vast amount of lifehistory variation; plant longevity, for instance, ranges from weeks to millennia (12). Many plant species' life cycles include cryptic life stages such as seedbanks (13) or dormant adults (similar to animal hibernation) (14). Reproduction also can be highly variable among plants, with seed mass and per-capita seed production ranging across six orders of magnitude (15).…”
mentioning
confidence: 99%
“…However, the plant kingdom encompasses a vast amount of lifehistory variation; plant longevity, for instance, ranges from weeks to millennia (12). Many plant species' life cycles include cryptic life stages such as seedbanks (13) or dormant adults (similar to animal hibernation) (14). Reproduction also can be highly variable among plants, with seed mass and per-capita seed production ranging across six orders of magnitude (15).…”
mentioning
confidence: 99%
“…Although the main benefits of vegetative dormancy have been suggested to be as a bet-hedging trait (Shefferson 2009), some have also suggested that no benefits may actually exist or that other ecological phenomena may conflate the observation of evolutionary impacts (Shefferson et al 2001, Gregg 2011. Vegetative dormancy likely functions differently in many species, and has likely evolved on many separate occasions (Shefferson 2009). Here, vegetative dormancy did not appear to function as a bethedging trait in the two long-lived perennial species that we studied.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, flowering probability increases with size (Kull 1999(Kull , 2002. Further, plants may forego sprouting for several years via vegetative dormancy, and the tendency to become vegetatively dormant decreases with increasing plant size (Shefferson 2009). Fruiting results in dust seeds, which germinate and develop into protocorms, a non-photosynthetic, immature life stage in which the orchid consumes carbon and all other nutrition from its mycorrhizal fungus (Rasmussen 1995, Kull 1999.…”
Section: Study Species and Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no completely achlorophyllous orchids known from EVER. Important here is that myco-heterotrophic orchids are known to go through periods of vegetative dormancy of one to 11 years (Shefferson 2009). It is thought that vegetative dormancy may allow orchids to recover from environmental stress, and if proper conditions are restored then flowering will re-occur.…”
Section: Terrestrial Orchidsmentioning
confidence: 99%